Experimenting different software architectures performance techniques a case study. - Balsamo, Simonetta (Software engineering notes.)
In this paper we describe our experience in performance analysis of the software architecture of the NICE ease study which is responsible for providing several secure communications in a naval communication system. We applied two complementary techniques, one based on stochastic process algebras and one based on simulation, in order to derive some performance indices at the software architectural level. The case study analysis allows us to point out the relative merit of the considered techniques including the performance model derivation, the type of analysis and performance results that we can carry out, and the feedback at the design level, e.g. performance results interpretation that we obtain. Finally, we discuss how to take advantage of the integration of different techniques in software architecture performance analysis.